Combined Secondary Ion Mass Spectrometry Depth Profiling and Focused Ion Beam Analysis of Cu Films Electrodeposited under Oscillatory Conditions. Issue 5 (11th February 2015) - Hai, Nguyen T. M.; Lechner, David; Stricker, Florian; Furrer, Julien; Broekmann, Peter
Abstract The recrystallization behavior of Cu films electrodeposited under oscillatory conditions in the presence of plating additives was studied by means of secondary ion mass spectrometry (SIMS) and focused ion beam analysis. When combined with bis‐(sodium‐sulfopropyl)‐disulfide (SPS), Imep levelers (polymerizates of imidazole and epichlorohydrin) show characteristic oscillations in the galvanostatic potential/time transient measurements. These are related to the periodic degradation and restoration of the active leveler ensemble at the interface. The leveler action relies on adduct formation between the Imep and MPS (mercaptopropane sulfonic acid)‐stabilized CuI complexes that appear as intermediates of the copper deposition when SPS is present in the electrolyte. SIMS depth profiling proves that additives are incorporated into the growing film preferentially under transient conditions during the structural breakdown of the leveler ensemble and its subsequent restoration. In contrast, Cu films electrodeposited in the presence of a structurally intact Imep–CuI–MPS ensemble remain largely contamination free.